Differences in JUUL Appeal Among Past and Current Youth JUUL Users. Issue 5 (28th November 2020) - Davis, Danielle R; Krishnan-Sarin, Suchitra; Bold, Krysten W; Morean, Meghan E; Jackson, Asti; Camenga, Deepa; Kong, Grace
Abstract: Introduction: JUUL, a closed system e-cigarette with disposable pods, is popular among youth, with positive attributes of this product linked to current use by youth. However, many youth try JUUL and do not continue using; understanding differences in the appeal of this device between current users and those who chose not to continue use can inform regulation and prevention efforts. The aim of the current study is to compare JUUL appeal in youth among past users (ie, used, but not in past month) and current users (ie, used in past month). Methods: A cross-sectional survey was conducted in four Connecticut high schools in Spring 2018. This survey assessed JUUL use and reasons for liking/disliking JUUL, including its' pharmacological effects (eg, nicotine "buzz"), product characteristics (eg, flavors), peer influence, appeal compared to other e-cigarettes, and concealability. Logistic regressions were conducted to examine differences in liking/disliking JUUL by use status (past vs. current). Results: Among JUUL users ( N = 1374; 43% of total sample), 30.4% were past users and 69.6% were current users. Compared to current users, past users were less likely to like JUUL for positive pharmacological effects (eg, nicotine "buzz"), product characteristics (eg, flavors), and peer use and more likely to dislike JUUL for the adverse pharmacological effects (eg, headache), product characteristics (eg, flavors), and for "other" reasons (open-ended response; eg, perceived harm). Conclusions: Findings suggest that altering JUUL appeal through regulating nicotine content and flavors may be key in policy aimed at shifting youth to become past JUUL users. Implications: This study investigates how current and past youth JUUL users differ in their report of the appeal of JUUL. Past users are less likely to report experiencing positive pharmacological effects and product characteristics of JUUL and are less likely to report appeal due to peer use. Understanding how appeal of JUUL may differ among past and current users can aid in our understanding of how to regulate these products so that they are less appealing to current youth users.